2008
DOI: 10.1001/archopht.126.9.1235
|View full text |Cite
|
Sign up to set email alerts
|

Patient Attitudes Toward Resident Involvement in Cataract Surgery

Abstract: To assess how patients in an academic ophthalmology practice feel regarding the involvement of residents in their cataract surgery. Methods: Using an anonymous survey, we asked patients with cataracts about issues related to resident involvement in cataract surgery, including informed consent, how likely they were to agree to resident involvement in their surgery, and the likelihood that they would seek care elsewhere if residents were to be involved in their surgery. Results: Participants indicated they shoul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…It is generally agreed that patients should be made fully aware of who is doing their procedure, particularly as their involvement increases . Most patients feel a general consent form is sufficient for residents’ presence in the operating room, but fewer agree it would suffice for assistance or performance of the surgery and prefer full disclosure instead …”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…It is generally agreed that patients should be made fully aware of who is doing their procedure, particularly as their involvement increases . Most patients feel a general consent form is sufficient for residents’ presence in the operating room, but fewer agree it would suffice for assistance or performance of the surgery and prefer full disclosure instead …”
Section: Discussionsupporting
confidence: 76%
“…Our report suggests that 54 of 96 patients (56.3%; 95% CI, 45.7%-66.4%) would consent with full disclosure. This is supported by other studies, both with surgeries and emergency department procedures . This was also seen in parental consent regarding their children, a situation which one might think even more sensitive .…”
Section: Discussionmentioning
confidence: 93%
“…Wisner and colleagues found that most patients are willing to agree to resident involvement in surgical procedures. 7 However, a study from the United States showed that participants have a low level of willingness to allow residents to perform invasive procedures. 1 In our study, the lowest percentages regarding residents' involvement in patient care were related to invasive tasks such as a skin biopsy and malignant tumor excision (37.6% and 29.5%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported variable results regarding patients' willingness to have residents perform their cataract surgery, ranging from very low (16%) to very high (95%). 11 12 13 14 One study reported a range of 21 to 86% even among patients living in the same geographic location. 13 Another study reported that although most patients are willing to have residents assist with their cataract surgery if patients are fully informed and asked in advance, one-quarter of these patients reported they would be likely or very likely to seek treatment elsewhere if residents were the primary surgeon of their cataract surgery.…”
mentioning
confidence: 99%
“… 13 Another study reported that although most patients are willing to have residents assist with their cataract surgery if patients are fully informed and asked in advance, one-quarter of these patients reported they would be likely or very likely to seek treatment elsewhere if residents were the primary surgeon of their cataract surgery. 14 …”
mentioning
confidence: 99%